Welfare analysis of the vehicle quota system in Beijing, Shanghai and Guangzhou - Ong, Min Qi (2016)
The rapid rise of vehicle ownership in China has raised concerns over road congestion and air pollution, with cities such as Shanghai, Beijing, and Guangzhou implemented their own unique Vehicle Quota System (VQS) to control vehicle growth. This paper sets out to evaluate the social welfare effects of the VQS in Shanghai, Beijing and Guangzhou, by making comparisons to the Singapore VQS, which is widely recognized for its efficiency. A theoretical analysis of the four VQS is first conducted, which proposes the ranking of efficiency as follows: Singapore > Shanghai > Guangzhou > Beijing. Following which, in accordance with Ng’s “a dollar is a dollar” theory, this paper focuses on quantifying the efficiency effects of the four VQS, while leaving the equity issue to a general taxation policy. The demand functions, both linear and isoelastic, for vehicle licenses in Singapore are postulated using the Certificate of Entitlement data obtained from the Land Transport Authority. Efficiency of Singapore’s VQS is estimated by the area under the demand curves, and welfare changes for simulated scenarios where Singapore adopts the different VQS are computed. Singapore’s VQS is found to have the highest efficiency while Beijing the least, with linear demand indicating a higher efficiency for Shanghai than Guangzhou and vice versa for isoelastic. This paper proceeds to make some policy recommendations, and suggests some possible areas of future research, which could provide some insights for emerging economies that consider enacting their own VQS.